L’image de l’imprévisible dans l’existence des personnages dans La valse aux adieux de Milan Kundera - Romaissa Djouadi; Zineb Moustiri (Multilinguales)
The post-Proustian period was marked by the disappearance of psychological realism and the illusion of reality which dominated the 19th century. This literary transition allows writers of the third era to return to the first modern texts, where the major themes are reinterpreted according to the reality of their society. One of the major themes of contemporary literary productions is that of the unpredictable, which arises from the adventures of Don Quixote. The writer Milan Kundera, inspired by the products of the first time, seeks to combine in his works the first modern existential reflections with the reality that marks his present. This is why the unpredictable was the essential subject of all his writings, including La valse aux adieux, where the eventualities of human existence are discussed. The interest of this study is to show how would Milan Kundera present the theme of the unpredictable in La valse aux adieux? Furthermore, how would Kundera explain the world of the unpredictable via his literary plot?